Fog computing based radio access networks：architecture，principles and challenges - Bonan YIN; Yuan AI; Mugen PENG (Dianxin kexue)
To reduce the burden of fronthaul link，avoid large-scale wireless signal processing in centralized baseband unit（BBU）pool，and take full advantage of processing and storage capabilities in edge devices，a fog computing based radio access network（F-RAN）was presented as an evolution form of heterogeneous cloud radio access networks.The core idea of F-RAN was to take full advantage of processing and storage capabilities in edge devices which could achieve the local distributed content delivery，the local distributed collaboration radio signal processing and the local distributed cooperative radio resource management functions.System architectures of F-RAN，promising key techniques，and researching open issues of F-RAN were discussed in detail.